Multiple mechanisms are involved in the acute vasodilatory effect of 17beta-estradiol in the isolated perfused rat heart. - Hügel, S; Neubauer, S; Lie, S; Ernst, R; Horn, M; Schmidt, H; Allolio, B; Reincke, M (1999)
The purpose of this study was to define the dose-dependent effects of 17beta-estradiol on coronary flow and cardiac function in isolated rat hearts and to identify the mechanisms involved in its vasodilator action. Hearts from female and male Wistar rats were perfused at constant pressure (100 mm Hg). Stereoisomer specificity and the mechanism of vasodilation by 17beta-estradiol were examined in female rat hearts. Function was measured by a left ventricular (LV) balloon and coronary flow (CF) with an ultrasonic flowmeter. 17Beta-estradiol at 10(-6), 5 x 10(-6), and 10(-5) M increased CF in female hearts by 5 +/- 2, 27 +/- 4 (p < 0.05 vs. baseline), and 40 +/- 4% (p < 0.05 vs. baseline), respectively. The effect of 17beta-estradiol in hearts from male rats was similar but less pronounced compared with females [deltaCF 8 +/- 3, 19 +/- 3 (p < 0.05 vs. baseline)] and 25 +/- 7% (p < 0.05 vs. baseline; p < 0.05 vs. female 17beta-estradiol). Maximum vasodilation by the stereoisomer 17alpha-estradiol was significantly smaller [deltaCF 5 +/- 3, 4 +/- 3 (p < 0.05 vs. female 17beta-estradiol) and 14 +/- 1% (p < 0.05 vs. baseline; p < 0.05 vs. female 17beta-estradiol)] for 10(-6), 5 x 10(-6), and 10(-5) M. Pretreatment with the NO-synthesis inhibitor Nomega-methyl-L-arginine (10(-4) M) had no effect on the maximal vasodilator response to 17beta-estradiol (10(-5) M) [deltaCF 36 +/- 6% (p < 0.05 vs. baseline)]. When hearts were pretreated with the prostaglandin-synthesis inhibitor diclofenac (10(-6) M), the maximal vasodilator effect of 17beta-estradiol was partially attenuated [deltaCF 12 +/- 7% (p < 0.05 vs. female 17beta-estradiol)]. Similarly, pretreatment with the K+ATP-blocker glibenclamide (10(-6) M) partially inhibited the maximal vasodilator effect of 17beta-estradiol [deltaCF 22 +/- 6% (p < 0.05 vs. baseline; p < 0.05 vs. female 17beta-estradiol)]. Pretreatment with the Ca2+ channel antagonist nifedipine (7.2 x 10(-8) M) completely blocked the vasodilator effect. In isolated perfused rat hearts, 17beta-estradiol induced marked acute coronary vasodilation; this effect is in part gender specific, and in female hearts, largely stereoisomer specific. The dilator effect is mediated predominantly by calcium channel blockade, but prostaglandin release and K+ATP channel activation also are involved. In the isolated perfused rat heart, NO production does not contribute to the acute vasodilator effect of 17beta-estradiol.